2021
DOI: 10.1371/journal.pone.0248332
|View full text |Cite
|
Sign up to set email alerts
|

Association of engagement in cultural activities with cause-specific mortality determined through an eight-year follow up: The HUNT Study, Norway

Abstract: Participation in cultural activities may protect against cause-specific mortality; however, there is limited knowledge regarding this association. The present study examines the association between participation in a range of receptive and creative cultural activities and risk of cardiovascular disease- and cancer-related mortality. We also examined whether participation in such activities and influence by gender have on this association. We followed 35,902 participants of the Nord-Trøndelag Health Study (HUNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…The Nord-Trøndelag Health Study (HUNT), a longitudinal study in Norway, reported that the frequency of social participation of less than 1, 1 to less than 2, and 2 or more times per week reduced mortality risk by 18%, 31%, and 39%, respectively [ 14 ]. Participation in both receptive and creative activities at least twice a week was associated with a 29% reduction in cancer-related mortality [ 15 ]. Fancourt et al studied the association of all-cause mortality among adults aged 50 years and older and reported that those who participated in receptive arts activities at least once every few months or more had a 31% lower mortality rate compared to those who never participated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Nord-Trøndelag Health Study (HUNT), a longitudinal study in Norway, reported that the frequency of social participation of less than 1, 1 to less than 2, and 2 or more times per week reduced mortality risk by 18%, 31%, and 39%, respectively [ 14 ]. Participation in both receptive and creative activities at least twice a week was associated with a 29% reduction in cancer-related mortality [ 15 ]. Fancourt et al studied the association of all-cause mortality among adults aged 50 years and older and reported that those who participated in receptive arts activities at least once every few months or more had a 31% lower mortality rate compared to those who never participated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular attendance of cultural events in the community has been shown to be associated with a multitude of health bene ts including increased longevity [25][26][27][28] and previous commentary has described the potential of the cultural heritage sector as providing sites for public health interventions [29]. DAC from cultural institutions such as museums, arts galleries and libraries has enormous potential for enabling wider access and more frequent and exible engagement for optimal public health impact.…”
Section: Discussionmentioning
confidence: 99%
“…Regular attendance of cultural events in the community has been shown to be associated with a multitude of health bene ts including increased longevity [38][39][40][41] and previous commentary has described the potential of the cultural heritage sector as providing sites for public health interventions [20]. OAC from cultural institutions such as museums, arts galleries and libraries, has enormous potential for enabling wider access and more frequent and exible engagement for optimal public health impact.…”
Section: Discussionmentioning
confidence: 99%